КИХ-фильтры с независимым управлением фазочастотной характеристикой - Ivanov, V. V.; Shakurskiy, V. K.; Shakurskiy, Shakurskiy M. V. (PE "Politekhperiodika", Book and Journal Publishers, 2012)
The structural realization of digital FIR-filters using frequency sampling with real time control of phase-frequency characteristic is considered. The characteristics of elementary digital filters, the algorithm of their output signals summation and the way of phase-frequency characteristic shift are given.